Optimising kinetics in the freestyle flip turn push-off - Lyttle, A.; Blanksby, B.; Elliott, B.; Lloyd, D. (1998)
INTRODUCTION: Turning technique is an important component in swimming performance with turn times positively correlating with final event time. However, little is known about the mechanics of an effective turn. This study sought to provide an exploratory analysis of how various kinetic and hydrodynamic variables during wall push-off are related to the wall exit velocity. METHODS: Thirty experienced male swimmers with body types of within one SD of the mean for selected anthropometric parameters reported for elite male adult swimmers (Mazza et al., 1994) were recruited for the study. During three freestyle flip turns, selected kinetic, hydrodynamic and kinematic variables of the wall pushoff were recorded. The wall push-off phase was measured from the point of maximum knee flexion during wall contact until the feet left the wall. Kinetics were recorded via a 2D vertically mounted forceplate which recorded peak push-off force and total impulse. The acceleration of each swimmer`s centre of gravity (CG) and wall exit velocity of the CG were calculated from underwater videography. Hydrodynamic peak drag force and drag impulse were calculated from the kinetic and kinematic data using a derivative of Newton`s second law. RESULTS: A stepwise regression was performed with wall exit velocity as the criterion variable and push-off time, peak propulsive force, total propulsive impulse, peak drag force, and total drag impulse as the independent variables. The stepwise regression yielded peak drag force, peak propulsive force and push-off time in the equation, with beta values indicating that the peak drag force carried the highest weighting of the three variables. CONCLUSIONS: The results of the stepwise regression indicated that an optimal combination of a low peak drag force, high peak propulsive force and increased wall time produced the fastest wall exit velocity. The inclusion of the peak drag force in the regression equation as the most important predictor of wall exit velocity highlights the importance of drag in turning technique. Factors such as very high push-off forces and exaggerated movements during wall push-off may lead to higher peak drag forces which, in turn, could be detrimental to the overall turning performance.